2020
DOI: 10.1186/s12872-020-01514-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between inflammation and skeletal muscle proteolysis, skeletal mass and strength in elderly heart failure patients and their prognostic implications

Abstract: Background Inflammation and skeletal muscle wasting often coexist in elderly populations, but few studies have examined their relationship in elderly heart failure (HF) patients. This study examined the relationship between inflammation and increased skeletal muscle proteolysis, reduced skeletal mass and strength, and their prognostic implications in elderly HF patients (> 65 years) using a random forest approach. Methods We prospectively enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
1
24
0
4
Order By: Relevance
“…Sarcopenia is a generalized and progressive disorder of skeletal muscle mass and is related to increased risk of adverse outcomes such as falls, fractures, physical frailty, and mortality in CKD patients ( 6 , 23 , 24 ). However, few studies had investigated the impact of PhA, Inflammatory Cytokines and ARBs-blockers, and sarcopenia prevalence in ND-CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is a generalized and progressive disorder of skeletal muscle mass and is related to increased risk of adverse outcomes such as falls, fractures, physical frailty, and mortality in CKD patients ( 6 , 23 , 24 ). However, few studies had investigated the impact of PhA, Inflammatory Cytokines and ARBs-blockers, and sarcopenia prevalence in ND-CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HD skeletal muscle is hyperexcitable, which can cause involuntary and prolonged contractions that may contribute to chorea [ 27 ] and could produce elevated levels of IL-6. However, it is also known that chronically elevated IL-6 production can promote skeletal muscle wasting [ 28 , 29 ] and muscular atrophy [ 30 ]. In addition to the general skeletal muscle dysfunction occurring in HD [ 5 , 31 , 32 , 33 ], skeletal muscle wasting and/or atrophy is likely to represent a significant component of HD pathogenesis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory activation with increased plasma/serum cytokine levels has been described as an important factor for the progression of chronic heart failure (CHF) (1,2). Cytokines appear to act as catabolic factors in the pathogenesis of skeletal muscle wasting and cardiac cachexia (3)(4)(5). This has important implications as muscle mass is an important determinant of exercise and functional capacity (6).…”
Section: Introductionmentioning
confidence: 99%
“…This has important implications as muscle mass is an important determinant of exercise and functional capacity ( 6 ). Moreover, the progressive loss of muscle mass, cachexia (i.e., weight loss due to an underlying illness), and low levels of muscular strength are strong predictors of the risk for premature mortality ( 5 , 7 , 8 ). Emerging research has demonstrated the important relationship between cytokines, health, and cardiovascular fitness.…”
Section: Introductionmentioning
confidence: 99%